Effects of Chinese Fir and Chinese Sassafras Plantations on Soil Biochemistry - Jiang, Pei-Kun (Indian Forester, 2002)
Potential degradation of soils under continuous Chinese fir (Cunninghamia lanceolata) monoculture has long been an economical and environmental concern in southeastern China where Chinese fir is the most important timber species. Previous studies have reported reduced nutrient availability and microbial vigour in such soils. To specify the causes of these deductions, soil samples from rhizosphere and adjacent rooting zone of neighbouring stands of Chinese fir and Chinese sassafras (Sassafras tzumu) of 20-year-old were analyzed and eompared for their chemical, biochemical and biological properties. The same analysis and comparison were also carried out for soil samples from first-crop plantation (where Chinese fir was planted for the first time) and second-crop plantation (where Chinese fir was planted again after harvesting). All samples were analyzed for humic acid carbon (HAC), total nitrogen (TN), HA:FA ratio (ratio of humic acid C to fulfic acid C) and C:N ratio (ratio of total organic C to total nitrogen) and microbial activities. The study revealed that HAC, HA : FA ratio and TN were much lower in Chinese fir stands than those in Chinese sassafras stands, while the C:N ratio was just the opposite. Without exception, bacteria, fungi and actinomyces were all more active in Chinese sassafras stands. The total microbial population was 1.58 times higher in rhizosphere of Chinese sassafras stands than that of Chinese fir. Correspondingly, enzymatic activities associated with urease, protease, sucrase and phosphatase followed similar pattern to microbial population, with respective 1.70, 1.78, 1.47 and 1.33 times higher in the former than the later. In contrast, the polyphenol oxidase activity was lower in the former than in the later. In general, continuous monoculture of Chinese fir resulted in deterioration in rhizosphere biologically and biochemically. The total population of rhizospheric microbes was reduced by 45% in the second-crop compared to the first-crop stands. Furthermore, continuous Chinese fir monoculture induced a decline in the proportion of bacteria to the total microbes number. Consequently, enzymatic activities except polyphenol oxidase decreased after continued Chinese fir monoculture. Urease, protease, sucrase and phosphatase were 31, 24 31 and 32% lower in the second-crop than in the first-crop stands, respectively. An accumulation of freephenol in the rhizosphere of second-crop stand, which is considered to be toxic to plant and soil microbes, were probably, at least partially, responsible for the growth decline in continuous Chinese fir monoculture plantations. Biological and biochemical deterioration in rhizospheric conditions was the major cause in the growth decline and soil degradation in continuous Chinese fir monoculture.